(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
Two decades after the “iconic turn” has been proclaimed, it still remains uncertain whether that expression catches a paradigm shift which has actually taken place or whether it only yet calls forth for it to happen. The essay takes a look at the different ways in which the expression might be understood, referring either to a kind of visual thinking, a disciplinary self-reflection or a epistemic meta-discourse. The success of the expression goes hand in hand, so it seems, with the uncertainty of its status, as still today, it is by no means evident to question the evidence of the image. Against the verdict of the philologist Ernst Robert Curtius, still echoing today, who claimed that, in contrast with the science of text, “the science of images is easy”, the essay advocates for three ‘turns of the screw’ in order to make image theory ‘more difficult’: the turn from an iconology to a symptomatology, from extensive to intensive and from indicative to conjunctive.